Carnitine palmitoyltransferase 1C: From cognition to cancer. (January 2016) - Casals, Núria; Zammit, Victor; Herrero, Laura; Fadó, Rut; Rodríguez-Rodríguez, Rosalía; Serra, Dolors
Abstract: Carnitine palmitoyltransferase 1 (CPT1) C was the last member of the CPT1 family of genes to be discovered. CPT1A and CPT1B were identified as the gate-keeper enzymes for the entry of long-chain fatty acids (as carnitine esters) into mitochondria and their further oxidation, and they show differences in their kinetics and tissue expression. Although CPT1C exhibits high sequence similarity to CPT1A and CPT1B, it is specifically expressed in neurons (a cell-type that does not use fatty acids as fuel to any major extent), it is localized in the endoplasmic reticulum of cells, and it has minimal CPT1 catalytic activity withl -carnitine and acyl-CoA esters. The lack of an easily measurable biological activity has hampered attempts to elucidate the cellular and physiological role of CPT1C but has not diminished the interest of the biomedical research community in this CPT1 isoform. The observations that CPT1C binds malonyl-CoA and long-chain acyl-CoA suggest that it is a sensor of lipid metabolism in neurons, where it appears to impact ceramide and triacylglycerol (TAG) metabolism. CPT1C global knock-out mice show a wide range of brain disorders, including impaired cognition and spatial learning, motor deficits, and a deregulation in food intake and energy homeostasis. The first disease-causing CPT1C mutation was recently described in humans, with Cpt1c being identified as the gene causing hereditary spastic paraplegia. The putative role of CPT1C in the regulation of complex-lipid metabolism is supported by the observation that it is highly expressed in certain virulent tumor cells, conferring them resistance to glucose- and oxygen-deprivation. Therefore, CPT1C may be a promising target in the treatment of cancer. Here we review the molecular, biochemical, and structural properties of CPT1C and discuss its potential roles in brain function, and cancer.